Deployment and Measurement of Quality of Service Parameters for Triple Play Services in Optical Access Networks - Jan Latal; Miroslav Kralik; Zdenek Wilcek; Jakub Kolar; Josef Vojtech (Communications - Scientific letters of the University of Zilina, 2017)
Broadband telecommunication networks are the future of communication and distribution of multimedia services. Thanks to the high transmission potential and capacity of optical fibres, the optical networks are predestined to be more widely used in telecommunications considering the higher data rates through Triple Play services. This paper describes the impact of selected quality parameters on multimedia services defined as Triple Play within an optical network based on the EPON standard. The Triple Play services are then evaluated with measuring instruments and software applications according to QoS requirements and using evaluation methods based on generally defined standards. These are mainly subjective (listening and conversational) and objective (MSE, PSNR, SSIM) methods, or parameters (MOS) and factors (bitrate, delay, packet loss rate, jitter, BER) that are defined for the respective service. The values measured during the experimental tests were related to the limiting parameters of optical topology based on EPON networks for individual services according to their QoS requirements and objective user evaluation.